Presenting the Development Model of Educational Organizations with Emphasis on the Entrepreneurship Drivers in Higher Education - Yazdani Ghadi, Sakineh; Jabbari, Negin; Azma, Fereydoon (Iranian Journal of Educational Sociology, 2022)
Purpose: The development of educational organizations plays an important role in creating a competitive advantage for organizations. Therefore, the aim of this study was to presenting the development model of educational organizations with emphasis on the entrepreneurship drivers in higher education.Methodology: This study in terms of purpose was applied and in terms of implementation method was descriptive from type of cross-sectional. The research population were included all faculty members of Golestan province universities, numbering 1023 people. The sample size was calculated based on Cochran's formula 279 people, which were selected by stratified random sampling method. The research tool was 80 question researcher-made questionnaire on the development of educational organizations with emphasis on entrepreneurial drivers, which whose content validity according to the opinion of experts was calculated as 0.74. Data were analyzed with exploratory factor analysis and structural equation modeling methods in SPSS-21 and Smart PLS-3 software.Findings: The findings showed that the development of educational organizations with emphasis on the entrepreneurial drivers had 80 items in 12 components and 5 dimensions. Dimensions were included entrepreneurial and knowledge-based education and research (with two components of entrepreneurial and knowledge-based research and entrepreneurial and knowledge-based education), structural-organizational (with four components of structure and organization, leadership management, human resources and financial resources and academic independence), technological development and growth (with one component of technological development and growth), policy making of science and technology and the governance system of the higher education system (with two components of development of entrepreneurial mission and perspective and policy making) and contextual factors (with three components of support factors, interaction and communication and cultural-social factors) which whose factor load of all was higher than 0.60, their average variance extracted was higher than 0.50 and their reliability with using Cronbach's alpha and combined methods was calculated higher than 0.70. Also, the development model of educational organizations with emphasis on the entrepreneurship drivers in higher education had a good fit. In addition, the development model of educational organizations with emphasis on the entrepreneurship drivers in higher education on each of the dimensions and each of the dimensions on its components had a direct and significant effect (P